ASSURING QUALITY IN FARM ANIMAL WELFARE CURRICULA: THE CASE OF WELFOOD CURRICULA - EVANGELIA N. SOSSIDOU; D. STAMATIS; E. SZŰCS; R. GEERS (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of the present study is to analyze virtual learning environments and to provide a framework for assuring quality in farm animal welfare curricula. The framework is constructed according to the experimental learning for a case study developed in the context of the Leonardo da Vinci Community Vocational Training Action Pilot Project entitled “WELFOOD-Promoting quality assurance in animal welfare-environment-food quality interaction studies through upgraded e-Learning”. WELFOOD addressed objectives such as improvement and competencies of the skills in vocational training to promote employability and facilitate integration and reintegration in terms of capabilities and knowledge, needed for improved technologies in animal husbandry and food industry.